The coincidence of Familial Mediterranean Fever and Hypereosinophilia in a patient with Hereditary Elliptocytosis - Muzaffer Keklik; Ali Unal; Serdar Sivgin; Olgun Kontas; Eray Eroglu; Semih Yilmaz; Leylagul Kaynar; Bulent Eser; Mustafa Cetin (Mediterranean Journal of Hematology and Infectious Diseases)
Familial Mediterranean fever (FMF) is a genetic disease with autosomal inheritance characterized by recurrent fever, abdominal pain, and serositis attacks. It is relatively common in the races and ethnical groups around Mediterranean Sea (Sephardic Jews, Armenians, Turks and Arabians). Hereditary elliptocytosis (HE) is common genetic defect of the red blood cell membrane skeleton. Spectrin mutations are the predominant causes of HE. Hypereosinophilia is defined as a number of eosinophil granulocytes equal or greater than 0.5 X 109 / liter or 500/ mm3 of circulating blood. The main causes are allergies and parasitic infections. This case report describes a Turkish female HE patient who presented with FMF and hypereosinophilia. Genetic analysis revealed heterozygous mutation in exon 10 of the MEFV gene (V726A). The patient was successfully treated with colchicine and steroid treatment with 3 months follow-up. To the best of our knowledge, this is the first report of association between FMF, HE, and hypereosinophilia.